HBRS 10 must reads 2020 - Schnaubelt, Teri; Menasche, Steve (Gildan Audio, 2019)
A year's worth of management wisdom, all in one place. We've reviewed the ideas, insights, and best practices from the past year of Harvard Business Review to keep you up-to-date on the most cutting-edge, influential thinking driving business today. With authors from Michael E. Porter to Katrina Lake and company examples from Alibaba to 3M, this volume brings the most current and important management conversations right to your fingertips. This book will inspire you to: ask better questions to boost your learning, persuade others, and negotiate more effectively; create workplace conditions where gender equity can thrive; boost results by allowing humans and AI to enhance one another's strengths; make better connections with your customers by giving them a glimpse inside your company; scale your agile processes from a few teams to hundreds; build a commitment to both economic and social values in your organization; and prepare your company for a rapidly aging workforce and society.